Cytoprotective activities of Polygonum minus aqueous leaf extract on ethanol-induced gastric ulcer in rats - Wasman, S.Q.; Mahmood, A.A.; Salehhuddin, H.; Zahra, A.A.; Salmah, I. (Academic Journals, 2010)
Polygonum minus is a medicinal plant commonly used in traditional medicine for the treatment of many aliments. The present study was performed to investigate anti-ulcer activity of P. minus aqueous leaf extract (PMALE) against ethanol-induced gastric ulcer in rats. Group 1 rats (ulcer control group) were pre-treated with vehicle (distilled water). Group 2 rats (reference group) were orally pretreated with 20 mg/kg omeprazole. Group 3 and 4 (experimental groups) were orally pre-treated with 250 and 500 mg/kg PMALE, respectively. After one hour later, all groups received absolute ethanol to generate gastric mucosal injury. After an additional hour, all the rats were sacrificed and the gastric juice was collected for determining of pH and mucous weight. The stomachs were examined for gastric ulcer areas. Grossly; the ulcer control group exhibited severe mucosal injury, whereas pre-treatment with either omeprazole or PMALE exhibited significant protection of gastric mucosal injury and increase in mucus production. Flattening of gastric mucosal folds was also observed in rats pretreated with PMALE. Histology, gastric wall of ulcer control group revealed severe damage of gastric mucosa, along with edema and leucocytes infiltration of the submucosal layer compared to rats pre-treated with either omeprazole or PMALE which showed marked gastric protection, reduction of edema and leucocytes infiltration of the submucosal layer. Acute toxicity study with a higher dose of 5 g/kg did not manifest any toxicological signs in rats. In conclusions, the present finding suggests that PMALE promotes ulcer protection as ascertained by the comparative decreases in ulcer areas, reduction of edema and leucocytes infiltration of the submucosal layer.